Hikmah Pensyariatan Hukum (Tasyrī’) pada Aspek Ayat Pidana: Studi Pemikiran Hasbi Ash-Shiddieqy - Ariani, Dina; Hadi, Sutrisno (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
The background of this research is because there are still many negative perceptions of the provisions of the Qur'an in the criminal field, which is mainly due to incomprehension of the wisdom of legal law in these verses. The purpose of the study was to comprehensively analyze Teungku Hasbi's exposure and thoughts in Tafsir an-Nūr regarding the wisdom of tasyrī' on several aspects of criminal law verses, namely adultery, qażf, drinking khamr, theft, muḥārabah, and al-baghyu. The choice of tafsir an-Nūr itself as the object of study is based on the author's expertise in the field of tafsir, the important position of this tafsir in the treasures of tafsir in Nusantara, and its complete discussion of thirty juz al-Qur'an. This research is a library research type with primary sources Tafsir an-Nūr. The data collection and processing method uses the qualitative data analysis (QDA) method with a content analysis approach. This study concludes that the presentation of Tafsir an-Nūr related to the issue of wisdom tasyrī' in criminal law verses has a strong argumentation basis, naqly and 'aqly. This can be observed from the sources he uses in verse understanding. In addition, his thinking was also oriented towards conveying the hidayah of the Qur'an to Muslims; In terms of originality and independence of his thoughts, Teungku Hasbi did not come out much from the previous mufassir exposure. He received considerable influence from Tafsir al-Marāghī, al-Manār, and Ibn Kasīr. Nevertheless, the independence of his thinking remains visible. This is evidenced by some of his opposing opinions with Jumhur ulama, such as about stoning for adulterers of muhsan that have expired and his thoughts on setting a minimum limit on the property of cutting off the hands of thieves handed over to the ruler.